The Role of Phosphorus in the Growth of Sal Forests in Jharkhand: A Comprehensive Review (International Journal of Food and Nutritional Sciences, 2022)
Sal forests (Shorea robusta) are a vital component of the Indian subcontinent's forest ecosystem, playing a crucial role in maintaining biodiversity and providing various ecosystem services. Jharkhand, located in eastern India, is home to significant expanses of Sal forests. This abstract provides an overview of the role of phosphorus (P) in the growth and development of Sal forests in the Jharkhand region. Phosphorus is an essential nutrient for plant growth and is often a limiting factor in forest ecosystems. The availability and distribution of phosphorus in the soil profoundly influence the health and productivity of Sal forests. This review examines the various ways in which phosphorus impacts the growth of Sal trees, the composition of the forest, and the overall ecosystem dynamics in the Jharkhand region.